FRP-concrete bond performance under accelerated hygrothermal conditions. (8th February 2021) - Mukhtar, Faisal M.; Peiris, Abheetha
Highlights: Temperature increased the FRP-concrete bond strength at low humidity within 5 weeks. Failure mode changed from substrate to adhesive-concrete interface at 100% RH. Bond strength was lowest (12% reduction) under alternating wet/dry cycles. Epoxy cured at 60 °C changed the failure mode with no effect on bond strength. Using degraded properties avoided overestimating bond strength of exposed specimens. Abstract: Drawing on information obtained via double lap shear tests, this paper discusses FRP-concrete bond behavior following five weeks of exposure to several accelerated hygrothermal conditions. Material tests were also carried out for both dry carbon fibers and the epoxy used in the bond study under similar hygrothermal conditions. The bond-slip relationship for the hygrothermal conditions were developed, and fracture energy calculated for the FRP-concrete bond. The use of degraded material properties obtained from material test coupons under the same exposure conditions prevented overestimation of the FRP-concrete bond fracture energy. Testing revealed that the FRP-concrete bond strength increased as temperature increased at low humidity (dry heat) — a potential consequence of alteration in the epoxy glass transition temperature. The bond strength of concrete with steel slag incorporated was superior at all temperatures and low humidity. In response to continuous or periodic submergence in water, specimen failure mode transitioned from substrate failure to adhesive-concrete interface failure. Alternating two-day wet/dry cycles resulted in a 12% drop of FRP-concrete bond strength. Under low humidity, the FRP dry fiber tensile stress increased as temperature increased (dry heat), while the opposite dynamic was observed in the epoxy coupons.